Joe DiLisio Sr observes his 86th birthday today! - McCumber, David (Raton Range Raton, New Mexico, 1978)
Newspaper Article on the 86th birthday of Joe DiLisio Sr..
Master list item #: 33
File location is in the Raton File Cabinet
Keywords: DiLisio, Joe Sr; International State Bank; University of Delaware; College of Santa Fe; Kiwanian; Knights of Columbus; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; Rome, Italy; Hartford, Connecticut; Trinidad, Colorado; Pittsburgh, Pennsivania; El Moro, Colorado; Gardener, New Mexico; Cimarron, New Mexico